Pengembangan Perbankan Syariah Dalam Mendukung Inklusi Keuangan di Indonesia - ainolyaqin, ainol yaqin (ITB AAS INDONESIA Surakarta, 2024)
The purpose of this journal is to examine the evolution of Islamic banking practices as a means of enhancing financial awareness in Indonesia. In order to increase the general public's access to products and financial services that are fair, affordable, and useful, they are referred to as financial inclusion. The Islamic banking system has become a crucial alternative in the Indonesian financial system. Deskriptif analysis is the research method used in this journal. Data are obtained through relevant secondary data sources and research studies. This analysis will show how Islamic banks operate in Indonesia, how Islamic banks maintain their financial integrity, and the problems that arise when they are expanding. Research indicates that the rise in Islamic banks has helped to increase awareness of money in Indonesia. However, numerous challenges are faced by the syariah banking sector. Several of these include inadequate infrastructure, inadequate knowledge about goods and services provided by Islamic banks, and regulations that have not yet fully addressed the root causes of the problem. Due to this, the journal also offers advice on how to resolve the issue and encourage the development of more sensitive Islamic banks in Indonesia.